2020
DOI: 10.1016/j.breast.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in Breast Cancer Survivors in the Middle East: A Retrospective Study

Abstract: Introduction By the time they complete breast cancer therapy, many young patients are still of childbearing age. We aim to estimate the incidence of pregnancies in women who completed treatment and examine the percentage of patients who received fertility counseling before initiation of therapy. Material and methods Electronic health records of breast cancer patients between 2008 and 2014 at AUBMC were screened for exclusion criteria of having metastatic disease or know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…These choices are obviously influenced by the patient's overall plans for parenthood. In a study conducted between 2018 and 2014 in a population similar to ours, Assi et al ( 15 ) reported that 30% of the 39 women in their small sample intended to become a parent at the time of diagnosis. We were not able to take this fundamental psychosocial factor into account, which constitutes a limitation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These choices are obviously influenced by the patient's overall plans for parenthood. In a study conducted between 2018 and 2014 in a population similar to ours, Assi et al ( 15 ) reported that 30% of the 39 women in their small sample intended to become a parent at the time of diagnosis. We were not able to take this fundamental psychosocial factor into account, which constitutes a limitation.…”
Section: Discussionsupporting
confidence: 55%
“…However, other proxies of the intention of women with breast cancer to become a parent have been used elsewhere, such as marital status. For example, in a study published in 2014 by Ruddy et al ( 15 ) concerning women < 45 years of age with breast cancer, 37% of those younger than 40 years of age intended before their diagnosis to give birth to a child. They also reported that married women were more concerned about the risk of post-treatment hypofertility than other women ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a study by Kopeika et al (29) in the UK also found that 41% of young breast cancer survivors showed tendency to have children. Similarly, a study by in Beirut, Lebanon, revealed that 30.76% of women wanted more children at the time of diagnosis (38).…”
Section: Discussionmentioning
confidence: 89%
“…Data corroborated by an American study with 211 women with breast cancer undergoing chemotherapy, where 52% did not receive advice on preserving fertility. 4 Also observed in a study conducted in Lebanon 20 with 39 women with breast cancer and 76.9% did not discuss with the oncologist the possibility of infertility.…”
Section: Discussionmentioning
confidence: 99%